Values of Local Wisdom: A Potential to Develop an Assessment and Remedial - Iwan Setia Kurniawan; Uus Toharudin (International Journal of Evaluation and Research in Education (IJERE), 2017)
This study aimed to describe the ability of student teachers of biology at Pasundan University in developing assessment and remedial based on local wisdom (local wisdom). This research uses descriptive quantitative and comparative approach, the data obtained by the data analysis described to obtain information or a description of these results, further students' ability in comparison. Tests of significance using parametric tests with two-tailed t-test. The population in this study as many as 197 students were divided into 38 groups, 38 groups divided into each of 19 groups and 19 groups remedial assessment. The sample in this research is divided each as much as 13 groups. Data collected by the non-test, the data obtained from a document or report student assignments given a score based on the indicators are divided into several aspects of assessment, data analysis was performed by descriptive statistical. The results showed that the ability of student teachers of biology in developing assessment based on local wisdom including both categories with an average score of 62.23. Remedial teacher's ability to develop based on local wisdom included in the category enough with an average score of 64.31. The highest average score for the assessment is on the aspects of integration of local wisdom values of 71.92 and the lowest score on the aspect of validity assessment amounting to 56.92. The highest average score for remedial namely the implementation aspects of 71.54 and the lowest scores on originality aspects of 53.38. The test results show that the significance of the t (t) of -0.488, t table (t table) two tails at 2.179. p-value of 0.635. Assuming that if t <t table (-0.488 <2.179) or with a p-value> 0.05 (0.635> 0.05) can thus be concluded that students in developing assessment and remedial based on local wisdom has the same ability.